Effect of genetic improvement of grain yield and nitrogen efficiency of mid‐season indica rice cultivars. Issue 2 (26th January 2015) - Liu, Lijun; Xiong, Yiwei; Bian, Jinglong; Zhang, Hao; Gu, Junfei; Wang, Zhiqin; Yang, Jianchang
Abstract: Genetic improvement (GI) of mid‐season indica rice ( Oryza sativa L.) in China has been experienced four typical plant types during the past several decades, i.e., early tall cultivars (ET), dwarf cultivars (DC), semi‐dwarf cultivars (SDC) and super rice cultivars (SR). However, little is known about the changes in fertilizer nitrogen (N) efficiency and their relationships with grain yield during the GI. With 12 representative mid‐season indica cultivars of the four types during GI, the effects of GI on grain yield and nitrogen efficiency were investigated. The results show that GI significantly increased grain yield and agronomic efficiency (AE) of N fertilizer but had no significant effect on recovery efficiency (RE) of N fertilizer. The low percentage of filled grains in modern SR limited its yield potential and the further increase in AE. GI decreased the N uptake from heading to maturity, leading to lower RE in modern rice cultivars. The rapid decline of the activities of root oxidation and nitrate reductase in SR during grain filling might be the physiological reasons for the lower percentage of filled grains and lower N uptake from heading to maturity.